Implementasi Algortima Kriptografi Rsa, Kompresi Data Huffman, Dan Steganografi Eof Pada Media Video Untuk Keamanan Data Di Pt Selaras Citanusa Wisata - Moch. Alfian Ichsan; Windarto Windarto (Sekolah Tinggi Teknik - PLN, 2017)
The rapid development of technology and information has an impact o to process of delivering data can be done through a variety of media one of which is an e-mail. Of course, the security of the data and information which transmitted is necessary and can not be ignored in order to maintain the confidentiality of such data. As a company engaged in the field of travel agency, PT Selaras Citanusa Wisata also use information and communication technology to produce several documents that must be kept from unauthorized person, one of which is the manifest of Hajj and Umrah pilgrims. To deal with the problems occured in PT Selaras Citanusa Wisata concerning the security of the data it needs a data security application to secure manifest of Hajj and Umrah pilgrims’ data. By applying RSA (Rivest Shamir Adleman), a cryptographic algorithm, Huffman compression algorithm combined with End of File steganography algorithms, the application is built in java programming language, desktop based. This application can secure and maintain the confidentiality of PT Selaras Citanusa Wisata data so as to prevent from theft and data manipulation by parties who do not have the authority.